The Development of Forced Degradation and Stability Indicating Studies of Drugs- A Review - Verma, Akanksha; Singla, Shivali; Palia, Priyankul (Asian Journal of Pharmaceutical Research and Development, 2022)
Force degradation study is an essential study that provides the knowledge & judgement to develop a stability indicating analytical method. This study helps to establish the specification and shelf life of a drug substance or drug product. Force degradation study show the chemical behaviour of the molecule which in turn helps in the development of formulation and package. This helps to describe the analytical methods helpful for development of stability indicating method. In addition, the regulatory guidance is very general and does not explain about the performance of forced degradation studies. Thus, this review discusses the current trends in performance of forced degradation studies by providing a strategy for conducting studies on degradation mechanisms and also describes the analytical methods helpful for development of stability indicating method.